Case report: A unique presentation of a high-grade neuroepithelial tumor with EWSR1::PATZ1 fusion with diagnostic, molecular, and therapeutic insights - Ene, Andre; Di, Jing; Neltner, Janna H.; Pittman, Thomas; Arnold, Susanne M.; Kolesar, Jill M.; Villano, John L.; Bachert, Sara E.; Allison, Derek B. (Frontiers in Oncology, 2023)
Background EWSR1::PATZ1 fusion tumors are exceedingly rare in the central nervous system with only 14 prior cases documented. PATZ1 fusion neuroepithelial tumors are beginning to be recognized as a distinct molecular class of neoplasms that most often occur in children and young adults. These tumors are polyphenotypic, show diverse morphologic features, may be low- or high-grade, and tend to have an intermediate prognosis. Case presentation Herein, we present an unusual case of a high-grade neuroepithelial tumor in a young man with an EWSR1::PATZ1 fusion. This case is unique because the tumor appears to have undergone high-grade transformation from a persistent low-grade glioma, which has yet to be reported. Furthermore, this case is the first to document concurrent RB1 loss, SMAD4 loss, and TP53 inactivation in this tumor type, which correlates with high-grade transformation. Fortunately, this patient is alive 2.5 years after treatment and 18.5 years after initial presentation, which provides a unique window into how these tumors clinically behave over a long follow-up period. Finally, we discuss the altered molecular pathways that are a result of the EWSR1::PATZ1 fusion and discuss potential therapeutic targets. Conclusion Awareness of the emerging entity of PATZ1 fusion neuroepithelial tumors is important not only for accurate diagnostic and prognostic purposes but also for predicting response to therapy.